Problems of Unification of the International Transport Law - Nadezda Aleksandrovna Butakova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article explores the development and unification of international transport law. The author analyzes the development and unification of the shipping law, as it was appeared before the other areas of transport law. The paper discuses the exceptions from carriers liability and the monetary limits of carriers liability prescribed in unimodal transport conventions. The author came to the conclusions in this article about ways of improving the current transport law.